ACCESS TO CAPITAL AND SMALL INDUSTRY PERFORMANCE IN PALU CITY - I Nengah Oka Smara Putra; Darman; Erwan Sastrawan Farid (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines how various sources of capital access influence the performance of small food industries in Palu City. Using a quantitative approach with 87 respondents and multiple linear regression analysis, the results indicate that overall capital access significantly influences small industry performance. Separately, internal capital, namely personal savings and business profits, and formal external capital through bank loans, were shown to have a positive and significant impact. Conversely, other sources of capital, namely cooperatives, online loans, social savings and credit, and government assistance, did not show a significant impact. These findings indicate that small industry performance is supported more by internal capital and bank financing than by other capital sources.